MANAJEMEN PENGETAHUAN DOSEN DALAM PEMBELAJARAN BAHASA ARAB DI JURUSAN PENDIDIKAN BAHASA ARAB UIN SUNAN KALIJAGA YOGYAKARTA (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
students who have deep thesis writing skillsArabic and the ability of students who havethe ability of the Arabic language comprehensively is still small. this becomes a homeworkgreat for PBA majors. Knowledge management as onealternative to reduce the ability gap of students canimplemented by doing good cooperation betweenfacilitator (lecturer) and student to share knowledge in class. Resultsresearch shows that lecturer knowledge management in the departmentPBA has occurred even though it still has to make improvements tocombination process. As for the implementation of deep knowledge managementArabic learning has not taken place maximally due to lackawareness to share knowledge between students.